2002
DOI: 10.1016/s0005-2736(02)00516-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the system L amino acid transporter in T24 human bladder carcinoma cells

Abstract: System L is a major nutrient transport system responsible for the Na(+)-independent transport of large neutral amino acids including several essential amino acids. In malignant tumors, a system L transporter L-type amino acid transporter 1 (LAT1) is up-regulated to support tumor cell growth. LAT1 is also essential for the permeation of amino acids and amino acid-related drugs through the blood-brain barrier. To search for in vitro assay systems to examine the interaction of chemical compounds with LAT1, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
105
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 36 publications
13
105
1
Order By: Relevance
“…In the present study, the mean SUV max of 18 F-FMT differed significantly between adenocarcinoma (mean, 1.6 6 0.8) and nonadenocarcinomatous disease (mean, 2.1 6 1.1; P 5 0.0031). LAT1 is widely expressed in primary human cancers and several cancer cell lines, where it has been shown to play essential roles in growth and survival (21)(22)(23)(24)(25). LAT1 is overexpressed in malignant tumors and is associated with tumor proliferation, angiogenesis, and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean SUV max of 18 F-FMT differed significantly between adenocarcinoma (mean, 1.6 6 0.8) and nonadenocarcinomatous disease (mean, 2.1 6 1.1; P 5 0.0031). LAT1 is widely expressed in primary human cancers and several cancer cell lines, where it has been shown to play essential roles in growth and survival (21)(22)(23)(24)(25). LAT1 is overexpressed in malignant tumors and is associated with tumor proliferation, angiogenesis, and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LAT1 is overexpressed in some tumor tissues [34,35] and is actively involved in the proliferation of vascular smooth muscle cells [36]. In order to investigate whether or not LAT1 is involved in the proliferation of breast cancer cells, we employed BCH, a selective inhibitor of LAT1 [37,38], to inhibit the proliferation of malignant MDA-MB-231 cells. In the presence of 10 mM BCH, the proliferation of MDA-MB-231 cells was significantly reduced in comparison with control cells grown in the absence of BCH at either 24 h or 48 h post-cell treatment (Fig.…”
Section: Blockade and Downregulation Of Lat1 Inhibits The Proliferatimentioning
confidence: 99%
“…Indeed, most cells activate various different systems that are required for amino acid transport (1). Among these systems, the system L-type amino acid transporter-1 (LAT-1) is up-regulated in human bladder carcinoma cells (2), esophageal adenocarcinoma (3), epidermoid carcinoma (4), oral squamous cell carcinoma (5) and liver cancer (6). On the other hand, another of the major amino acid transport systems, system A, catalyses the transport of most of the small aliphatic amino acids including alanine, serine and glutamine (1).…”
Section: Introductionmentioning
confidence: 99%